2023
DOI: 10.3390/v15040953
|View full text |Cite
|
Sign up to set email alerts
|

Novel Putative Tymoviridae-like Virus Isolated from Culex Mosquitoes in Colombia

Abstract: The family Tymoviridae comprises positive-sense RNA viruses, which mainly infect plants. Recently, a few Tymoviridae-like viruses have been found in mosquitoes, which feed on vertebrate sources. We describe a novel Tymoviridae-like virus, putatively named, Guachaca virus (GUAV), isolated from Culex pipiens and Culex quinquefasciatus species of mosquitoes and collected in the rural area of Santa Marta, Colombia. After a cytopathic effect was observed in C6/36 cells, RNA was extracted and processed through the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The specific conditions of the shared environment could explain the similarities observed in the viromes of different mosquito species co-occurring in the same habitat. These conditions could potentially act as a selective pressure on mosquitoes, a concept proposed in a recent study in Colombia 40 . These findings are in line with metatranscriptomic analyses of the virome of Culex mosquitoes ( Cx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific conditions of the shared environment could explain the similarities observed in the viromes of different mosquito species co-occurring in the same habitat. These conditions could potentially act as a selective pressure on mosquitoes, a concept proposed in a recent study in Colombia 40 . These findings are in line with metatranscriptomic analyses of the virome of Culex mosquitoes ( Cx.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other ISVs with low representation (Fig. 3 ), such as Uxmal virus, Tanay virus, Cordoba virus, and Castlerea virus , from the Negevirus genus, are phylogenetically related to plant viruses 51 , 52 , suggesting the adaptation of plant viruses in insects that feed on plant fluids, possibly through selection pressure processes 40 . It is noteworthy that the ISVs detected in this study have been reported with a wide geographic distribution and a broad range of mosquito host species, including Aedes, Culex, Ochlerotatus, and Mansonia 27 , 45 , 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISVs have been described in the Birnaviridae, Bunyaviridae, Mesoniviridae, Negeviridae, Nodaviridae, Reoviridae, Rhabdoviridae, Togaviridae, Tymoviridae, and Flaviviridae families. They only infect insects and are vertically transmitted (Bolling et al, 2015 ; Hoyos-López et al, 2016 ; Guzman et al, 2018 ; Salim Mattar and Marco González, 2018 ; Öhlund et al, 2019 ; Laiton-Donato et al, 2023 ).…”
Section: Mosquitoes and Arbovirusmentioning
confidence: 99%